Interspeech 2016 2016
DOI: 10.21437/interspeech.2016-1199
|View full text |Cite
|
Sign up to set email alerts
|

Congruency Effect Between Articulation and Grasping in Native English Speakers

Abstract: Previous studies have shown congruency effects between specific speech articulations and manual grasping actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Similar facilitation effect is observed between backward-directed manual movement and articulation of the rounded back-mid vowel [o] . Moreover, similarly to the articulation-grip effect, this reach effect can be found in Finnish and Czech speakers (Vainio et al, 2015;Tiainen, et al, 2017b).…”
Section: Behavioral Evidence For Interaction Between Arm Movements Anmentioning
confidence: 58%
See 2 more Smart Citations
“…Similar facilitation effect is observed between backward-directed manual movement and articulation of the rounded back-mid vowel [o] . Moreover, similarly to the articulation-grip effect, this reach effect can be found in Finnish and Czech speakers (Vainio et al, 2015;Tiainen, et al, 2017b).…”
Section: Behavioral Evidence For Interaction Between Arm Movements Anmentioning
confidence: 58%
“…The articulation-grip effects introduced above that link certain vowels ([i] and [ɑ]) and consonants ([t] and [k]) to the precision and power grips were originally observed in Finnish speakers (Vainio et al, 2013). However, the same effects have been, so far, also replicated in Czech speakers (Tiainen, Lukavský, Tiippana, Vainio, Šimko, Felisberti, & Vainio, 2017b). The fact that the same effects can be observed in two separate languages that belong to .…”
Section: Behavioral Evidence For Interaction Between Grasping and Conmentioning
confidence: 85%
See 1 more Smart Citation
“…Rather, this directional information appears to be implicitly included in planning tongue movements required for producing specific vowels: the participants were mostly not aware that production of the vowels that they had to pronounce were differentially associated with fronting and backing. In addition, although the effect was originally observed in Finnish speakers [6], it has been, so far, also replicated in Czech speakers [8]. The fact that the same effects can be observed in two separate languages that belong to differentiated language families (Finnish is a Finno-Ugric/Uralic language, and Czech is a Slavic/Indo-European language) suggests that people have an implicit and language-independent tendency to link production of front vowels to forward-directed hand movements and back vowels to backward-directed hand movements.…”
Section: Introductionmentioning
confidence: 86%
“…The fact that the same effects can be observed in two separate languages that belong to differentiated language families (Finnish is a Finno-Ugric/Uralic language, and Czech is a Slavic/Indo-European language) suggests that people have an implicit and language-independent tendency to link production of front vowels to forward-directed hand movements and back vowels to backward-directed hand movements. Finally, the effect cannot be observed when articulation requires moving the tongue backward or forward in order to produce the dorsal consonant [k] performed by raising the tongue body toward the back of the velum or the coronal consonant [t] produced by fronting the tongue tip toward high-front position [8]. Hence, Vainio et al [7] suggested that this effect is exclusively linked to fronting and backing the tongue body for vowel production rather than shaping the tongue in order to articulate the consonants such as [t] and [k].…”
Section: Introductionmentioning
confidence: 99%